When we were young [compact disc, unabridged] : a novel - Kingsbury, Karen (Kingsbury, Karen. Baxter family., 2018)
Married couple Noah and Emily have decided to call it quits, and Noah is leaving in the morning. Emily's friend Kari prays for a miracle. But deep inside, Kari knows she needs a miracle herself.